Black Women’s Radical Religious Epistemologies in Mahogany and Steepled Towers - CL Nash; Carol Marie Webster; Geeta Patel (African Journal of Gender and Religion (AJGR))
The essays in this issue explore the diverse ways in which Black women’s religious epistemologies challenge conventional theological narratives. From the African spiritualities of Nigeria and Jamaica to the anti-colonial politics of Senegal, Sudan, and South Africa, the contributors offer a rich tapestry of perspectives highlighting the radical nature of Black women’s religious knowledge production. Weaving an eclectic spectrum of spiritual practices and beliefs, these essays offer the basis of radical religious epistemologies that enable Black women living under a range of circumstances, in several regions of the world, to find a pathway through the virulence they inhabit within their everyday lives.